Analysis Of The Difficulties Of Student Learning Mathematics In Online Learning In The Pandemic Time Covid-19 - Rifqi Amir Kurnia; Bettin Dian Wahyuni; Nopi Handayani; Yoza Nopita Sari (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to analyze the impact of COVID-19 on students' mathematics learning difficulties in online learning at school. The research conducted was qualitative research. The data collection method used is the interview method with the interview guide instrument. Meanwhile, the data analysis technique used is to use interactive techniques with three procedures. Based on the results of an interview by one of Bengkulu City's SMPN 4 students named Muhammad Radja Al-Farabi, he experienced difficulties in learning mathematics online, difficulty in focusing on learning mathematics, and difficulty in getting internet network access.